2012
DOI: 10.1089/cyber.2011.0140
|View full text |Cite
|
Sign up to set email alerts
|

The Present and Future of Positive Technologies

Abstract: The goal of this work is to delimit the field of Positive Technology--the scientific and applied approach to the use of technology for improving the quality of our personal experience. This new field combines the objectives of Positive Psychology with enhancements of Information and Communication Technologies (ICTs) by focusing on three key variables--emotional quality, engagement/actualization, and connectedness--that are able to transform our personal experience in a tool for building new and enduring person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(94 citation statements)
references
References 59 publications
0
82
0
12
Order By: Relevance
“…In this same issue of CYBER, Botella et al 73 further define this view by discussing the links between existing technologies and the Positive Technology framework described here. For now, we welcome you to Positive Technology.…”
Section: Discussionmentioning
confidence: 99%
“…In this same issue of CYBER, Botella et al 73 further define this view by discussing the links between existing technologies and the Positive Technology framework described here. For now, we welcome you to Positive Technology.…”
Section: Discussionmentioning
confidence: 99%
“…Our research team is working in the study of the effect of positive affect in the treatment of mental and health problems and in the use of technology to promote well-being (positive technology). [33] Ninety-five participants were eligible, but 34 were not allocated to the conditions for several reasons (see flow diagram in Figure 1). The main reason for the nine dropouts before allocation was that the participants found that if they would be allocated to the VRAM condition, the treatment sessions involved too much time (twice a week) and they were not ready to commit to it.…”
Section: Introductionmentioning
confidence: 99%
“…Amazon's Echo and Belkin's Crock Pot slow cooker, for example, are part of this domain and represent a category that is growing. These products are designed purely to extend the potential for material consumption, but much of the smart domestic technology currently in use or in development is intended for positive (Botella, Riva, Gaggioli, Wiederhold, Alcaniz and Baños 2012) or transformative (Mick 2006) use. This focuses on the enhancement of either human or ecological states, with personal well-being its aim.…”
Section: Defining Smart Domestic Products (Sdps)mentioning
confidence: 99%